Immune Tolerance Induced Using Plasma Exchange and Rituximab in an Infantile Pompe Disease Patient. (June 2014) - Deodato, Federica; Ginocchio, Virginia Maria; Onofri, Alfredo; Grutter, Giorgia; Germani, Alessandro; Dionisi-Vici, Carlo
Infantile Pompe disease, resulting from deficiency of lysosomal acid α-glucosidase, requires enzyme replacement therapy with recombinant human acid α-glucosidase. Most patients develop antirecombinant human acid α-glucosidase antibodies, leading to reduced response to enzyme therapy in a subgroup of them. Aiming to improve treatment response, several immune tolerance induction strategies have been explored. We describe a patient with life-threatening infusion-associated reactions presenting anti-recombinant human acid α-glucosidase antibodies. He was successfully treated with an immune tolerance induction protocol, consisting of plasma exchange combined with a single dose of rituximab. Immediate reduction of antibody titer was obtained and enzyme therapy was resumed without infusion-associated reactions. Twenty-two months later, immunoglobulin G titer remained below 1:100. In conclusion, we applied a short-course immune tolerance induction strategy in a patient with severe infusion-associated reactions and anti-recombinant human acid α-glucosidase antibodies, leading to early and persisting reduction of antibody titer, in the absence of significant adverse events.